KONSEP RUMAH TANGGA DALAM AL-QURAN STUDY TAFSIR AYAT 34 SURAH AN-NISA TERHADAP TAFSIR AS-SA’DI - Try Ahmad Prasetio (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
In essence, marriage is the door for the meeting of two hearts in the shade of social life that lasts for a long time, in which there are various rights and obligations that each party must carry out to get a decent, happy, harmonious life, and get a good life. good lineage. Marriage is a strong bond based on a very deep feeling of love from each party to get along in order to maintain human continuity on earth. The Qur'an which contains instructions, and guidelines for all humans, has explained how the right way is in fostering the life of a family so that it is full of blessings and grace from Allah SWT. This study aims to determine the concept of household in the Qur'anic study of interpretation of verse 34 of Surah An-Nisa to the interpretation of As-Sa'di. This study uses library research methods, and uses a descriptive qualitative approach. The analysis in this study uses qualitative data that is presented without calculating numbers. And the results of this study indicate that it is important to maintain the rights and obligations of each family member in forming an ideal family. This also shows that Allah's Shari'a has explained to humans how to build a harmonious family. The ideal family will only be realized if family members can fulfill their obligations to Allah, themselves, their families, society and the environment, according to the teachings of the Qur'an and the guidance of the Prophet Muhammad.